Mediation of achievement motivation on the relationship between emotional intelligence and work discipline on employee performance - Risa Pusvitasari; Moh Mukhsin; Ali Imron (Jurnal Mantik, 2023)
The problem that is often faced by companies in achieving goals is the poor performance of employees. The purpose of this study is to analyze a model that is expected to improve employee performance by involving emotional intelligence and work discipline with achievement motivation as intervening variables in inpatient nurses at XYZ Hospital . The research method is quantitative by using a questionnaire with an interval scale of 1-10 with a sample of 115 employees from a population of 314 employees to test the five (5) predetermined hypotheses. The sructural equation model-partial least square (SEM-PLS) model was used to test the statistical significance of the path coefficient. The results of this study explain that emotional intelligence has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance, emotional intelligence has a positive and significant effect on achievement motivation, work discipline has a positive and significant effect on employee performance, and achievement motivation has a positive effect and significant to employee performance.